DEIXIS ANALYSIS IN THE SHORT STORY THE WOMAN WHO LOST IN THE PATCHOUMI GARDEN - Ray, Sukma Adelina; Yulianda, Asri (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2025)
This study analyzes the function of deixis (person, place, and time) in the short story